PENGARUH VOLUME PERDAGANGAN TERHADAP RETURN SAHAM DENGAN TRADING DAY SEBAGAI VARIABEL MODERATING PADA PERUSAHAAN PROPERTY & REALESTATE DI BURSA EFEK INDONESIA PERIODE 2010-2014 - Setiawan, Dedi (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2016)
The aim of this research is to analyze the influence of trading volume activity to stock return and the influence of trading day as the moderating variable in relations between trading volume activity and stock return. The samples of this research are the property and realestate firms listed in Indonesian Stock Exchange 2010 until 2014. The samples are collected using simple random sampling and result 155 firms fulfilling criterion as this research sample. Data analyzed by classic assumption tests and examination hypothesis by moderated regression analysis.The results of this research show that trading volume